INSURANCE RISKS OF MANAGEMENT IMPORTANT METHOD - Tugizova Malika Sokhib kizi (Journals Park Publishing, 2023)
Risk means the risk of losses arising from the nature of natural-climatic, economic and social events the possibility is understood. Historical, legal, economic or financial category of risk as a broad concept as seeing exit possible.
Keywords: economic theory, insurance risk, risks classification.